2018
DOI: 10.1016/j.amjmed.2018.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones and Risk of Atrial Fibrillation Among Patients with Diabetes and Coronary Disease

Abstract: We did not find a significant reduction of atrial fibrillation incidence with use of thiazolidinediones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…reported that the use of TZD was associated with a 24% reduction in the risk of incident AF compared with other antidiabetic drugs as second-line treatment among T2DM patients [ 38 ]. However, no significant differences in the risk of incident AF with use of TZD were reported in the PROactive, RECORD, and BARI 2D trials [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that the use of TZD was associated with a 24% reduction in the risk of incident AF compared with other antidiabetic drugs as second-line treatment among T2DM patients [ 38 ]. However, no significant differences in the risk of incident AF with use of TZD were reported in the PROactive, RECORD, and BARI 2D trials [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective study, the Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI 2D) study of patients with T2DM and documented coronary artery disease did not show a significant reduction in the incidence of NAF in those using metformin and/or the thiazolidinedione rosiglitazone. In the intention‐to‐treat analysis, the incidence of NAF was 87 per 1000 person‐years, with metformin and/or rosiglitazone compared to 95 per 1000 person years with insulin and/or a secretagogue (HR, 0.80; 95% CI, 0.43‐1.3; P = 0.3) . As the PROactive study, the BARI 2D study was not designed to investigate AF and, unlike the PROactive study, the thiazolidinedione rosiglitazone, and not pioglitazone, was used.…”
Section: Effect Of Drugs Used To Treat Type 2 Diabetes On Atrial Fibrmentioning
confidence: 98%
“…In the intention-to-treat analysis, the incidence of NAF was 87 per 1000 person-years, with metformin and/or rosiglitazone compared to 95 per 1000 person years with insulin and/or a secretagogue (HR, 0.80; 95% CI, 0.43-1.3; P = 0.3). 63 As the PROactive study, the BARI 2D study was not designed to investigate AF and, unlike the PROactive study, the thiazolidinedione rosiglitazone, and not pioglitazone, was used. A similar study, the RECORD study, was a prospective, blinded, placebo-controlled study of the addition of rosiglitazone to existing sulfonylurea or metformin therapy.…”
Section: Drugs That Lower Insulin Resistancementioning
confidence: 99%
“…Thiazolinediones are peroxisome proliferator-activated receptor-γ agonists, which decrease glucose levels by increasing storage of fatty acids in adipocytes, also decrease incidences of atrial fibrillation onset, which might also be influenced by their anti-inflammatory actions (Chao et al, 2012 ; Pallisgaard et al, 2017 ; Zhang Z. et al, 2017 ). However, other studies have shown in patients with coronary disease, thiazolinediones have no improvements in atrial fibrillation compared with other diabetes treatments including metformin, insulin, sulfonylurea or meglitinides, suggesting that the anti-inflammatory effects of thiazolinediones does not further improve anti-arrhythmia effects of controlling glucose levels (Pallisgaard et al, 2018 ).…”
Section: The Impact Of Diabetes Therapies On Arrhythmiasmentioning
confidence: 99%